FUNCTIONS OF LANGUAGE TOOLS - Ibragimova Iroda Artikmashrabovna (Scholar Express Journal, 2022)
The article enlightens ideas about the functions of linguistic means. The classifications of the world's linguists, the sequence of ideas, the classifications of the expressive, appellative, representative functions of language are analyzed
Keywords: Linguistic tools; language functions; expressive function; appellative function